The E-wallet effect a study on college students' usage of e-wallet in Iloilo City in relation to consumer spending and saving behavior - Panganiban, Rubbee; Ymalay, Bethel Dawn.; Young, Nathalie Shane (2024.)
E-wallets, otherwise known as a digital wallets in simple terms, are online payment tools used for the purpose of conveniently storing money, checking balances if bank accounts are linked into it, sending payments, receiving cash, and other cashless transactions. Many countries around the world have egun going cashless with the use of e-wallets. This study analyzes the preference of the college students towards e-wallets, their perception, and their consumer activity while using e-wallets. It explores the use of e-wallets of college students in Iloilo City in relation to their spending and saving behavior. The results help both marketers and businesses in the future in providing information about demographics, consumer activity, perspectives, preferred payment methods, spending and saving behavior, and height of frugality. By utilizing e-wallets, they offer more value, engaging surprises, incentives, and rewards to their target market. These objectives will be observed throughout the study's data collection and analysis process. The data were analyzed using SPSS statistical tool, frequency analysis.percentage, and Spearman correlation. marketers and businesses are recommended to observe changes in saving behavior over time as students increasingly adopt cashless payment methods and examine the role of financial education in saving behavior.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, July 2024..